The Moral Economy and Industrial Politics in the UK from the 1960s to the 1980s. Issue 40 (September 2019) - Phillips, Jim
Abstract : The 'moral economy perspective' has enriched a number of recent analyses in the history of industrial relations. Focusing on perceptions of fairness helps to explain the reasoning and activism of workers and trade-unionists engaged in industrial politics, movements and protests. A moral economy framework seems particularly apt where activists were animated by a sense of the established order being disturbed and dismantled by employers and policy-makers. Working-class and trade-union responses to the loss of industrial employment from the 1960s to the 1980s were often articulated in terms of collective injustice. Examination of these responses has been influenced by the works of E. P. Thompson and Karl Polanyi. Seeing the erosion of manual employment and changing working-class organization through the twin frameworks of deindustrialization and the moral economy is more productive than older and arguably dead-end narratives of economic decline and trade-union defeat.